Study on the Reaction Kinetics of Sulfur Mustard, Nitrogen Mustard and Their Chosen Analogues with Sodium Ethoxide - Klaudia Kozon; Jakub Nawała; Paweł Sura; Stanisław Popiel (Molecules)
The course and kinetics of the reactions of sulfur mustard, nitrogen mustard and their selected analogues with sodium ethoxide were studied using a gas chromatograph coupled with a mass spectrometer. 2-chloroethyl ethyl sulfide (CEES), a monofunctional analogue of sulfur mustard (HD), bis(2-chloroethyl) ether (BCEE), an oxygen analogue of sulfur mustard, and bis(2-chloroethyl)amine, an analogue of nitrogen mustard HN-3, in which one hydrogen atom remains unsubstituted with a chloroethyl group, were used as imitators of mustards. For the study, the last mentioned compound was given the acronym HN-0. The research included checking how the form of sodium ethoxide influences the reaction rate. Two solutions were used: sodium ethoxide solution obtained by dissolving a commercially available compound in crystalline form and ethoxide solution obtained by dissolving sodium in ethanol. Additionally, the extent to which diethylenetriamine (DETA) accelerates the reactions of the studied compounds with sodium ethoxide was checked. The decontamination reactions were carried out in an anhydrous environment at a constant temperature of 25.0 °C. The rate of the mustard decontamination reaction increased significantly in systems containing DETA. Therefore, this amine can be used as a catalyst for this reaction. DETA has the most significant effect on the rate of the reaction of sodium ethoxide with CEES. The effect of the EtONa form was tested in the decontamination reaction of HD, revealing that both forms are equally effective, with only minor differences in reaction rates. Freshly synthesised sodium ethoxide reacts with HD 1.24 times faster. The study also assessed whether selected non-CWA compounds can be successfully used in studies as mustard imitators. Nitrogen mustard and bis(2-chloroethyl)amine reactions proceed according to the same mechanism—nucleophilic substitution. Bis(2-chloroethyl)amine reacts slightly faster than HN-3, both in solution with and without the addition of a catalyst. Sulfur mustard (HD) and CEES with sodium ethoxide and DETA undergo an elimination reaction, while BCEE undergoes a substitution reaction, which proceeds much slower. The observed differences disqualify BCEE as a sulfur mustard imitator. HD and CEES react with sodium ethoxide and DETA so quickly that the exact kinetic parameters under the developed experimental conditions could not be determined.